2004
DOI: 10.1076/ceyr.28.2.145.26235
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prematurity on tear production

Abstract: Preterm infants have significantly reduced tear secretion compared with term infants. Postconceptional age, rather than birth weight, seems to be more correlated with the tear secretion. Sex and laterality does not appear to have an effect on tear production in infants. Tear production of preterm infants is significantly reduced than that of term infants during the first two months of life. Term infants increased their tear production significantly in each examination during the neonatal period while the prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Similar results were showed in neonate dogs (Silva & Galera 2004) and cats (unpublished results), indicating that in this period, the eye and adnexa are not completely developed. In human beings, however, only preterm infants secret lower amount of tears in comparison to term infants (Toker et al 2002, Akar et al 2004, Dogru et al 2004. Schirmer tear test-1 values of goats with 45, 180 and 549 days of age ranged from 8 to 35mm/min.…”
Section: Discussionmentioning
confidence: 95%
“…Similar results were showed in neonate dogs (Silva & Galera 2004) and cats (unpublished results), indicating that in this period, the eye and adnexa are not completely developed. In human beings, however, only preterm infants secret lower amount of tears in comparison to term infants (Toker et al 2002, Akar et al 2004, Dogru et al 2004. Schirmer tear test-1 values of goats with 45, 180 and 549 days of age ranged from 8 to 35mm/min.…”
Section: Discussionmentioning
confidence: 95%
“…infants <38 weeks of age at birth) have significantly reduced tear secretion compared with term infants (i.e. infants >38 weeks of age at birth) 14–16 . By 4 weeks after birth, 87% of term and 20% of preterm infants have normal adult tear flow 15 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that basal tear production is present in newborns [3,16,21], but it has also been described that magnitude of lacrimal secretion in the neonate is roughly the lower limit of the normal adult range [1,14]. Moreover, neonates and infants in the first months of life are known to have a highly stable precorneal tear film associated with very low spontaneous blink-rates [11].…”
Section: Introductionmentioning
confidence: 99%